Assessment of the Level of Expression Activity and Localization of Cd-Receptors in the Postmenopausal Period - Marina B. KHAMOSHINA; Dmitry P. PUGA; Bogdan O. SHCHEGLOV; Irina P. KOVAL; Ivan V. REVA; Svetlana N. SHCHEGLOVA; Galina V. REVA; Kirill V. STEGNIY (Modern Medicine)
The cervical mucosa (CM) is a critical site in the female reproductive system, but despite extensive histological studies in reproductive-age women, there is a notable gap in our understanding of the local immune homeostasis in postmenopausal women. This lack of knowledge is particularly concerning given the pivotal role of immune phenotypes in regulating neoangiogenesis during malignancy. Furthermore, the reasons underlying the inadequate immune response in carcinogenesis remain elusive. In this study, the authors aimed to address these knowledge gaps by investigating the local immune homeostasis (LIH) of CM in postmenopausal women. Their findings revealed age-related and localized features in the LIH of CM, shedding light on the complex interplay between the immune system and cervical tissues. Understanding these unique immune dynamics has far-reaching implications for the field of gynecology. The identification of age-related variations in LIH has significant implications for the development of conservative treatment strategies, prevention of complications, and early diagnosis of malignancy in postmenopausal women. By unraveling the intricate relationship between immune responses and cervical mucosal changes, this research provides a foundation for developing targeted interventions to enhance immune surveillance and bolster the body’s natural defenses against malignancies in this vulnerable population. In conclusion, this study underscores the importance of investigating the immune microenvironment of CM in postmenopausal women. The newfound knowledge regarding age-related and localized features in LIH not only advances our understanding of cervical health but also paves the way for more effective prevention, treatment, and early detection strategies, ultimately improving the overall quality of care for postmenopausal women at risk of cervical malignancies.